Senescence in Pulmonary Fibrosis: Between Aging and Exposure - Venosa, Alessandro (Frontiers in Medicine, 2020)
To date, chronic pulmonary pathologies represent the third leading cause of death in the elderly population. Evidence-based projections suggest that >65 (years old) individuals will account for more than a quarter of the world population before the turn of the century. Genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, deregulated nutrient sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, and altered intercellular communication, are described as the nine 'hallmarks” of cellular fitness. Any deviation from the normal pattern initiates a complex cascade of events culminating to a disease state. This blueprint, originally employed to describe the changes of cancer cells, can be also used to describe aging and fibrosis. Pulmonary fibrosis (PF) is the result of a progressively aberrant resolution process stemming from biological aging or exogenous stress. Environmental, dietary or occupational exposure accelerates the pathogenesis of a senescent phenotype based on 1) window of exposure; 2) dose, duration, recurrence; and 3) primary cells type being targeted. As the lung ages the threshold to generate an irreversibly senescent phenotype is lowered. In this review, we provide an assessment of the literature that interrogates lung epithelial, mesenchymal, and immune senescence at the intersection of aging, environmental exposure and pulmonary fibrosis.